2014
DOI: 10.1007/s10120-014-0337-3
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic pylorus-preserving gastrectomy for early gastric cancer in the middle stomach: technical report and surgical outcomes

Abstract: Introduction The feasibility, safety, and improved quality of postoperative life following laparoscopy-assisted pylorus-preserving gastrectomy (LAPPG) with a hand-sewn anastomosis via a mini-laparotomy for early gastric cancer (EGC) have been previously established. Here we describe the surgical procedure of totally laparoscopic pylorus-preserving gastrectomy (TLPPG) using an intracorporeal delta-shaped anastomosis technique, and the short-term surgical outcomes of 60 patients with EGC in the middle stomach ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…PPG was first performed as a treatment for gastric ulcers in 1967 [24]. Recently, LPPG has become one of the surgical modalities used for early gastric cancer to reduce invasion [8,17,[25][26][27]. However, the clinical significance of the CBVN preservation, which has an advantage in distal gastrectomy, has not been clear in PPG [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPG was first performed as a treatment for gastric ulcers in 1967 [24]. Recently, LPPG has become one of the surgical modalities used for early gastric cancer to reduce invasion [8,17,[25][26][27]. However, the clinical significance of the CBVN preservation, which has an advantage in distal gastrectomy, has not been clear in PPG [14].…”
Section: Discussionmentioning
confidence: 99%
“…The LPPG technique consisted of the following procedures, as previously described [6,17], with D1+ lymphadenectomy performed according to the 2nd edition of the Japanese Classification of Gastric Cancer (JCGC) [19]. A summary of our LPPG procedures is as follows: (1) the greater omentum was dissected; (2) the right gastroepiploic vein and artery were divided while preserving the infrapyloric vessels to maintain blood supply to the remaining pyloric cuff; (3) the suprapyloric lymph nodes were picked up if required, and the right gastric artery and the pyloric branch of the vagal nerve were preserved; (4) the lesser omentum was dissected, and the hepatic branch of the vagal nerve was preserved; (5) the trunk of the left gastroepiploic artery and vein were divided; (6) the greater curvature was rolled up toward the abdominal wall, and the suprapancreatic lymph nodes along the common hepatic artery and splenic artery were dissected; (7) when the CBVN was not preserved, the root of the left gastric artery was divided; (8) when the CBVN was preserved, the CBVN was made visible from the left side of the gastropancreatic ligament, the left gastric artery was divided at the distal site where the CBVN met, the CBVN was carefully skeletonized using an ultrasonically activated device so as not to cause thermal injury [20], and the posterior gastric branch of the vagal nerve was cut [17]; (9) the cardiac lymph nodes and the lymph nodes along the lesser curvature of the stomach were dissected; and (10) the stomach was transected 3-5 cm proximal to the pylorus and at the proximal site of the tumor, depending on the negative-confirmation biopsy. After the transection of the stomach, a gastro-gastro anastomosis was made by hand-suturing or using a linear stapler.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…During LAPPG, anastomosis can be easily performed directly from the small upper abdominal middle incision, as the site for anastomosis site is immediately under the incision for hand-sewn procedures. In reports of complete intracorporeal anastomosis during LAPPG, delta- shaped anastomosis was performed with demonstrated feasibility and safety in initial experiences ( Figure 2) (14,15). Conversely, reports of intracorporeal end-toend anastomosis after LAPPG were also published, where anastomosis was performed using a combination of a stapler and a hand-sewn procedure (16).…”
Section: Laparoscopic Procedures In Ppgmentioning
confidence: 99%
“…PPG for EGC in the middle portion of the stomach, with the distal tumor border at least 4 cm proximal to the pylorus, has been recognized as a modification of resection for EGC (8). However, using the laparoscopic approach for PPG is difficult because it should preserve the pyloric and hepatic branches of the vagus nerve and infrapyloric vessels (49)(50)(51). In Japan, Jiang et al reported a retrospective analysis of the postoperative outcomes of 307 laparoscopic-assisted pylorus-preserving gastrectomies (LAPPG) (52).…”
Section: Laparoscopic Function-preserving Surgerymentioning
confidence: 99%